1997
DOI: 10.1109/49.564133
|View full text |Cite
|
Sign up to set email alerts
|

Multicast routing with end-to-end delay and delay variation constraints

Abstract: We study the problem of constructing multicast trees to meet the quality of service requirements of real-time, interactive applications operating in high-speed packet-switched environments. In particular, we assume that multicast communication depends on (a) bounded delay along the paths from the source to each destination, and (b) bounded variation among the delays along these paths. We rst establish that the problem of determining such a constrained tree is NP-complete. We then derive heuristics that demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(91 citation statements)
references
References 12 publications
0
90
0
1
Order By: Relevance
“…Most of previous research on finding a multicast tree considers only one or two QoS constraints, like delay and jitter [8,9,10,11]. As far we know, only two methods have been published [6,13] recently for the MCMT problem.…”
Section: Introductionmentioning
confidence: 99%
“…Most of previous research on finding a multicast tree considers only one or two QoS constraints, like delay and jitter [8,9,10,11]. As far we know, only two methods have been published [6,13] recently for the MCMT problem.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the loss constraint (11) is equivalent to the delay constraint of DVBMT, while the loss variation constraint (12) is equivalent to the delay variation constraint of DVBMT. We have proved [23] that the DVBMT problem is NP-complete whenever the size of the destination set | M |≥ 2. Consequently, if we ignore the power loss due to the splitting of the optical signal at the branch nodes of the light-tree, the PCLT problem is also NP-complete.…”
Section: A the Pclt Problem Under Power Attenuation Onlymentioning
confidence: 99%
“…The degreeconstrained Steiner tree problem [4], [5] , in which it is assumed that some nodes may not support multicast (i.e., they cannot be used as branching points) or have a limited fanout capability has also been studied and appropriate heuristics have been proposed. A constrained multicast tree problem in which the objective is to to bound both the end-to-end delay and the delay variation among all source-destination paths has also been studied [23]; the total cost of the tree was not considered in that work, but it was shown that constructing such a constrained tree is an NP-complete problem.…”
Section: ) the Steiner Tree Problemmentioning
confidence: 99%
See 2 more Smart Citations